Does patient coaching make a difference in patient-physician communication during specialist consultations? A systematic review. Issue 5 (May 2017) - Alders, Irèn; Smits, Carolien; Brand, Paul; van Dulmen, Sandra
Highlights: Patient coaching seems a promising intervention to improve communication. Effective seems multiple coaching encounters to prepare and rehearse questions. Also effective seems evaluating the consultation and reflecting upon it. Audio recording during the consultation seems helpful. The evidence on effective elements in patient coaching is limited. Abstract: Objective: To systematically review the literature on the effectiveness of a patient coach intervention on patient − physician communication in specialists consultations. Methods: PubMed, Cochrane, PsycInfo, Cinahl and Embase were searched until November 2015. Included were papers describing interventions directed at adult outpatients in secondary care with a variety of somatic diseases. Outcomes had to be measured in communication effectivity from a patient's perspective. Results: Seventeen publications met the inclusion criteria (involving 3787 patients), describing 13 unique interventions. Most interventions were single one-on-one sessions taking between 20 and 40 min before consultation. Research quality in ten studies was high. These studies showed significant improvement on immediate, intermediate and long term patient − physician communication. Conclusion: We found limited evidence suggesting an improvement of patient − physician communication by having multiple patient coaching encounters during which questions are prepared and rehearsed and consultations are evaluated and reflected upon, sometimes supported by audio recording the consultation. Practice implications: The results of this review contribute to the (re-)design of an effective model for patient coaching, a profile and training approach of patient coaches. Future research should aim at determining which patients will benefit most from coaching interventions.